Design and development of a low-cost prosthesis directed to the activity with a gasoline brush cutter: A case study - Ferrari, Daniel [UNESP]; Bonfim, Gabriel [UNESP]; Oliveira, Raphael; Paschoarelli, Luis [UNESP]; Santos, João [UNESP] (Springer Nature, 2017)
In Brazil, the rate of people with disabilities resulting from amputation is relevant. The distribution of high-tech prostheses only meets a small portion of the population. On the other hand it is known that most of the industrialized products design in the world are developed to users considered “normal”. This study proposed, through guidance to a group of technical students, the design and development of a low-cost prosthesis to an individual with disarticulation of the left wrist, seeking to provide opportunities for the subject to conduct a vegetation cutting activity with a gasoline brush cutter. Based on the knowledge assimilated during the technical course in mechanics, the group of students explored new possibilities of alternative materials and processes in the search for an affordable solution. The project resulted in a prosthesis that attends the anatomical, mechanical and functional needs required by the individual X product interface.
Keywords: Inclusive design; Low cost; Prosthesis